LAMA3 overexpression enhances proliferation, migration and invasion in esophageal squamous cell carcinoma based on bioinformatics and experimental validation - Xia Wu; Qian Li; Junbin Wang; Lei Li; Mingtang Zuo; Yufeng Cheng (Scientific Reports)
Abstract Esophageal squamous cell carcinoma (ESCC) is a highly lethal malignancy and remains a major public health burden worldwide, particularly in China, where both incidence and mortality rates are among the highest globally. Recent studies suggest that laminin subunit alpha 3 (LAMA3), a component of the basement membrane, may promote tumor progression; however, its specific role in ESCC remains unclear. In this study, we analyzed public RNA-sequencing data from TCGA and TIMER to evaluate LAMA3 expression and its clinical relevance in ESCC. We also validated LAMA3 protein and mRNA expression in clinical samples and cell lines using immunohistochemistry and RT-qPCR. Using siRNA, we established LAMA3-knockdown ESCC cell models and assessed cell proliferation, colony formation, migration, and invasion in vitro. LAMA3 expression was 2.4-fold higher in ESCC tumor tissues than in adjacent normal tissues (p < 0.001). High LAMA3 levels were associated with worse overall survival and disease-free survival (p < 0.05). Knockdown of LAMA3 suppressed cell proliferation by 57% (p < 0.001), migration by 49% (p < 0.001), and invasion by 47% (p < 0.001).Pathway enrichment analysis indicated involvement of LAMA3 and its co-expressed genes in cell adhesion, extracellular matrix organization, and the PI3K-AKT pathway. In summary, our results demonstrate that LAMA3 is a major promoter of ESCC progression and a potential biomarker and therapeutic target.